TESTING THE LEVEL OF PHYSICAL HEALTH OF PRESCHOOL CHILDREN TO CORRECT THE SPORTS AND RECREATION ACTIVITIES - M.N. Kuznetsova; S.D. Polyakov; N.S. Podgornova; A.M. Sobolev (Педиатрическая фармакология, 2011)
The paper presents an assessment of the physical health of children 4–7 years old, brought up in Moscow children’s educational institutions. Statistically significant positive dynamics of indicators of physical development and functional training has been showed. Introduction of corrective exercises to the recreational and educational complex for children in low-and below-average levels of motor function helps improve the motor skills. Key words: preschool children, physical health, physical development, functional fitness. (Pediatric Pharmacology. — 2011; 8 (5): 66–69.)